2016
DOI: 10.1080/13607863.2016.1247416
|View full text |Cite
|
Sign up to set email alerts
|

Coping strategies in Spanish older adults: a MIMIC model of socio-demographic characteristics and activity level

Abstract: There is a complex relationship between socio-demographic characteristics, activity level and the coping strategies used by the elderly. It is important to understand this relationship in order to identify older adults who use ineffective coping, and to subsequently include them in intervention programs to improve their coping abilities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“…Understanding the nature and causes of feelings and being competent in emotional regulation skills reduces the likelihood of collapse under pressure. Furthermore, EI facilitates the use of proactive measures to restore emotional balance (Fernández-Berrocal and Extremera, 2006), and it is a positive predictor of feelings associated with well-being (Sánchez-Álvarez et al, 2016;Zeidner et al, 2016) and a negative predictor of phenomena associated with mood disorders (Rubio et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Understanding the nature and causes of feelings and being competent in emotional regulation skills reduces the likelihood of collapse under pressure. Furthermore, EI facilitates the use of proactive measures to restore emotional balance (Fernández-Berrocal and Extremera, 2006), and it is a positive predictor of feelings associated with well-being (Sánchez-Álvarez et al, 2016;Zeidner et al, 2016) and a negative predictor of phenomena associated with mood disorders (Rubio et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Anxiety is a complex feeling of worry about future events associated with uncertainty and a lack of managing a situation [36]. Several studies have found an association between anxiety symptoms and bodily pain [6,22,37,38]. In addition, anxiety and bodily pain are strongly prevalent problems, which affect the HRQoL of the older population [36], specifically in regard to mobility problems and physical health [4,37].…”
Section: Discussionmentioning
confidence: 99%
“…First, PA is associated with a higher level of social relations with other people, and the effects on health are obvious because anxiety is combated with social support and social events decrease the risk of experiencing chronic bodily pain (21). Secondly, previous studies have indicated that being physically active together, with healthy notions learned by older people, is associated with active coping strategies and, therefore, the reduction of bodily pain perception is evident [6,31,54]. Finally, PA and health education through specific social programs produce positive behavioral changes in psychological variables and HRQoL, such as bodily pain and physical components [55].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations